Natural Language Understanding for Chinese-based Service Robots - Bian, Ganghui; Gao, Chenjun; Che, Wenkai; Yanzhi, Dong; Yuan, Xiaohu; Liu, Huaping (2022 International Conference on Automation, Robotics and Computer Engineering (ICARCE), 2022)
Service robots have been used in a large number of practical applications, and in recent years there has been an increasing amount of research work on human-robot interaction. In the field of human-robot interaction, the problem of natural language understanding for robots is crucial, and there is very little research on natural language understanding for robots in Chinese. In this paper, we propose a framework for understanding the Chinese language-based robot navigation commands and verify their effectiveness.